The Design and Implementation of Waycryptic, a Versatile Cryptographic File System for Linux (in Chinese) - Lin, Haoxiang; Dong, Yuan; Zhang, Wei; Zhang, Suqin; Hu, Changjun (Journal of Chinese Computer Systems, 2007)
Recently it has been a focus to protect personal sensitive information. Using cryptographic technique is a promising way. This paper describes the design and implementation of Waycryptic, a versatile cryptographic file system for Linux. By integrating cryptographic technique into file system level, users obtain transparent, dynamic, efficient and secure encryption function without modifying their applications. Encrypted files could be saved on any physical file system which supports extended attributes (XATTR). Waycryptic also permits encrypted files to be shared among multi users and to be easily recovered by designating an account in advance. The results of Iozone and Bonnie benchmarks show that Waycryptic is comparatively efficient and is suitable for personal or multi-user systems which require enhanced security.